Malícia honey (Mimosa quadrivalvis L.) produced by the jandaíra bee (Melipona subnitida D.) shows antioxidant activity via phenolic compound action in obese rats - Maria Luiza Rolim Bezerra; Maria Luiza Rolim Bezerra; Mirela Gouveia-Nhanca; Mirela Gouveia-Nhanca; Maria Letícia da Veiga Dutra; Maria Letícia da Veiga Dutra; Kamila Sabino Batista; Alana Natalícia Vasconcelos de Araújo; Alana Natalícia Vasconcelos de Araújo; Marcos dos Santos Lima; Marcos dos Santos Lima; Mateus Duarte Ribeiro; et al. (Frontiers in Nutrition)
Background and aimsObesity is a disease associated with increased oxidative stress in humans and animals, and consumption of antioxidant compounds such as polyphenols can minimise it. These compounds are abundant in malícia (Mimosa quadrivalvis L.) honey produced by stingless bees. This study aimed to evaluate whether administration of Mimosa quadrivalvis L. honey to obese rats could reduce oxidative stress in vital organs through phenolic compound action.MethodsWistar rats (228 ± 14.69 g) were randomly divided into two groups: a healthy group (HG, n = 20) fed a control diet and an obese group (OG, n = 20) fed a cafeteria diet for the initial 8 weeks. After this period, these groups were again randomised into four subgroups: healthy (HG, n = 10), obese (OG, n = 10), healthy with malícia honey administration (1,000 mg/kg; HGH, n = 10), and obese with malícia honey administration (1,000 mg/kg; OGH, n = 10) for the final 8 weeks fed the previously mentioned diets. The rats were euthanised at the end of the experiment to collect brain, gut, kidney, and liver tissues to evaluate parameters related to oxidative stress and phenolic profile.ResultsThe administration of malícia honey reduced energy intake and weight gain in the OGH in comparison to the OG. Total antioxidant capacity increased in the brain, liver, and gut in both groups treated with honey compared to respective controls. Lipid peroxidation decreased in the brain, gut, and kidney of the OGH. Both treated groups showed elevated phenolic compound deposition, including catechin, procyanidins, and flavonoids, across all organs. Specifically, the brain in the OGH showed greater procyanidin B2 and gallic acid deposition; the liver showed increased procyanidin B1 and B2, epicatechin, and myricetin concentrations; the gut showed higher procyanidin B2 and kaempferol 3-glucoside concentrations; and the kidneys had increased catechin, procyanidin B1 and B2, and gallic acid deposition compared to the OG.ConclusionHistologically, the OGH displayed reduced neuronal damage and prevention of hepatic steatosis induced by the cafeteria diet. Malícia honey effectively reduced oxidative stress via modulation of phenolic compounds in the brain, gut, kidney, and liver of cafeteria diet-induced obese rats.